Matrix pencil method‐based reference current generation for shunt active power filters. Issue 4 (27th February 2018) - Terriche, Yacine; Golestan, Saeed; Guerrero, Josep M.; Kerdoune, Djallel; Vasquez, Juan C.
Abstract : In recent years, the shunt active power filters (SAPFs) have received much attention for compensating the harmonic pollution and also providing the reactive content. A crucial issue in controlling the SAPF is generating the reference compensating current (RCC). Typical approaches for this purpose are using the discrete Fourier transform (DFT) in the frequency domain or the instantaneous p–q theory and the synchronous reference frame in the time domain. The DFT, however, suffers from the picket‐fence effect and spectral leakage. On the other hand, the DFT takes at least one cycle of the nominal frequency. The time‐domain methods show a weakness under voltage distortion, which requires prior filtering techniques. The aim of this study is to present a fast yet effective method for generating the RCC for SAPFs. The proposed method, which is based on the matrix pencil method, has a fast dynamic response and works well under distorted and unbalanced voltage. Moreover, the proposed method can estimate the voltage phase accurately; this property enables the algorithm to compensate for both power factor and current unbalance. The effectiveness of the proposed method is verified using simulation and experimental results, and compared with the standard methods.